Synthesis and antiviral activity of N9-[3-fluoro-2-(phosphonomethoxy)propyl] analogues derived from N6-substituted adenines and 2,6-diaminopurines - Baszczyňski, Ondřej; Jansa, Petr; Dračínský, Martin; Klepetářová, Blanka; Holý, Antonín; Votruba, Ivan; de Clercq, Erik; Balzarini, Jan; Janeba, Zlatko (Bioorganic & medicinal chemistry, 2011)
An efficient method for the synthesis of N(9)-[3-fluoro-2-(phosphonomethoxy)propyl] (FPMP) derivatives of purine bases has been developed. Both (R)- and (S)-enantiomers of the N(6)-substituted FPMP derivatives of adenine and 2,6-diaminopurine were prepared and their anti-human immunodeficiency virus (HIV) and anti-Moloney murine sarcoma virus (MSV) activity was evaluated. Whereas none of the 6-substituted FPMPA derivatives showed any antiviral activity, several FPMPDAP derivatives had a moderate antiretroviral activity. Moreover, the data obtained from the study of the substrate activity of the active derivatives towards N(6)-methyl-AMP aminohydrolase support the notion that the studied N(6)-substituted FPMPDAP derivatives act as prodrugs of the antiretroviral FPMPG analogues.
Keywords: Animals; myši inbrední C3H; Antiviral Agents; Moloneyho virus myšího sarkomu; 3T3 Cells; vztah mezi dávkou a účinkem léčiva; Mice, Inbred C3H; Adenine; antivirové látky; Moloney murine sarcoma virus; 2-aminopurin; puriny; Structure-Activity Relationship; HIV-1; lidé; Mice; kultivované buňky; myši; krystalografie rentgenová; 2-Aminopurine; Cells, Cultured; organofosfonáty; Dose-Response Relationship, Drug; adenin; HIV-2; buňky 3T3; Purines; vztahy mezi strukturou a aktivitou; zvířata; Crystallography, X-Ray; Organophosphonates; Humans